I Implementasi Pendekatan Culturally Responsive Teaching Berbasis Media Wayang Tanah Liat Warak Ngendok Pada Materi dongeng Untuk Meningkatkan Hasil Belajar Dan Kreatifitas Siswa Kelas 2 A SDN Srondol Wetan 06 Semarang. - Rohmah, Siti Latifatur; Armawati, Heny Yuli; Kiptiyah, Siti Maryatul (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
This study aims to improve learning outcomes and student creativity in Indonesian language subjects of fairy tale material lifted from Semarang City icons through the Culturally Responsive Teaching (CRT) approach using Warak Ngendog Clay Puppet Media in Class IIA SDN Srondol Wetan 06, Semarang City. This type of research is called PTK. The subjects of this research amounted to 28 students in class II A SDN. This data analysis technique is called N-test gain. Data collection techniques include observation sheets and tests. The results showed an increase in learning outcomes with each cycle. The increase was shown by the average value in cycle I, which was 43%, cycle II, which was 71%, and cycle III, which was 96%. There was a significant average increase from cycle I to cycle II of 28% and from cycle II to the end of cycle III of 25%. Based on the final results of the research as a whole, it shows that the use of the Culturally Responsive Teaching (CRT) approach using Wayang Warak Ngendog media from Clay improves learning outcomes in fable sub-material fairy tales in Class 2A students of SDN Srondol Wetan 06.